The Effect of Being in Mother’s Hug on Neonates’ Pain during Immunization - Bagheriyan, samaneh; Miri, sakineh; Tehrani, hadi; Babaei heydarabadi, akbar (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: Pain is a complex phenomenon, which in the past were easily overlooked in infants. Pain relief is a basic need and rights of all human beings. The most obvious and most effective strategy for reducing neonatal pain and painful process of restricting the use of drugs and non-pharmacological methods of pain relief. The aim of this study was to examine the effect of being in mother’s hug on neonates’ pain during immunization Materials and methods: Mothers of 60 infants 2 to 4 months of your infant for vaccination were brought to health centers were invited to cooperate in the investigation. Samples were available. Infants were randomly divided into two groups of mothers and infants in arms control were. Data collection tools included a demographic questionnaire; Modified Behavioral Pain Scale. Data analysis using descriptive and inferential analyzes were conducted. Results: There were significant differences in Behavioral Pain Scores of two groups include: facial expression, cry, and movements (p<0.001). Conclusion: Findings regarding severity of pain in infants in the control group compared to the intervention group, Shows that Parents can be fed in order to reduce pain during painful procedures using safe and simple way to encourage. Key Words: Pain, Immunization, Neonate